Oryza cystatin 1 based genetic transformation in soybean for drought tolerance - Mangena, Phetole (My University, 2015)
Soybean is an important source of high quality protein and oil for both humans and animals, especially in protein formulations for pharmaceutical and nutriceutical use. This crop is adversely affected by both biotic and abiotic stresses impacting on its productivity. Soybean productivity can be improved via techniques such Agrobacterium-mediated genetic transformation. Soybean is recalcitrant and depends on suitable explants from which new shoots can be regenerated and be amenable for transformation. The goal of this study was to produce transgenic soybean plants that are tolerant to drought stress through Agrobacterium tumefaciens-mediated transformation. Multiple shoot induction on double and single coty-node explants, obtained from soybean seedlings derived from seeds germinated in vitro on Murashige and Skoog culture medium supplemented with cytokinins was studied. The effect of different concentrations of benzyladenine (1.57, 2.00 and 4.00 mg/l), and benzyladenine (2.00 mg/l) in combination with kinetin (1.00 mg/l) was tested. The results show that the double coty-node explants produce the highest number of shoots per explant, an average of 7.93 shoots on Murashige and Skoog medium supplemented with 2.00 mg/l benzyladenine. The lowest number being 1.87 shoots obtained from single coty-node explants cultured on Murashige and Skoog medium containing 4.00 mg/l benzyladenine. The single coty-node explants showed lower frequency (10–57%) of shoot induction when compared to the double coty-node explants (50–83%). The suitability of aminoglycoside antibiotics (hygromycin, tetracycline and rifampicin) for efficient elimination of Agrobacterium tumefaciens after co-cultivation was tested using a well agar diffusion assay. Co-culturing double coty-node explants with Agrobacterium containing pTF 101 vector carrying the Oryza cystatin 1 gene resulted in 76.6, 63.3 and 60.0% shoot regeneration on Murashige and Skoog shoot induction media (shoot induction medium 1, shoot induction medium 2 and shoot induction medium 3) containing hygromycin, tetracycline and rifampicin at 500 mg/l respectively. These antibiotics showed the highest zones of inhibition against pTF 101 using the well agar diffusion assay. On the other hand, 85% plant regeneration was obtained during in vivo transformation following Agrobacterium injection into seedlings. These results imply that vi both in vitro and in vivo protocols were suitable for transgenic shoot regeneration and plant establishment since all the plants continued surviving in the presence of 6.00 mg/l glufosinate-ammonium. Future work will focus on screening of transgenic plants using beta-glucuronidase and isolating the protein encoded by the Oryza cystatin 1 gene to further confirm the generation of transformed plants carrying the gene of interest.
Thesis (MSc. (Botany)) -- University of Limpopo, 2015
Keywords: Soybean; Drought tolerance; Soybean -- Breeding.; Crops -- Drought tolerance.